P59 Treatment and Drug Surveillance of Latent Tuberculosis Infections (LTBI) by a TB Pharmacist: A pilot study. (19th November 2012) - Abunga, YO; Brij, SO; Luwemba, G
Abstract : Objectives: To assess the safety and effectiveness of a pharmacist-led LTBI clinic. Methods: Patients identified by screening as having LTBI were seen by TB pharmacist at the weekly TB clinic. Initial interview included history of symptoms to exclude active TB. Baseline bloods were taken as well as a screen for blood borne viruses. Follow up appointments were scheduled at 2 weeks, one month and at the end of treatment. The TB pharmacist obtains written consent for therapy, dispenses medication and information leaflets regarding potential drug adverse effects. At follow-up appointments the pharmacist evaluates treatment adherence and potential adverse effects. Results: 62 latent TB patients were seen from 01/05/11 to 01/05/12. All patients were discussed at the TB-MDT. 51 (82%) patients were allocated to the pharmacist led clinic. The 11 (18%) patients seen by the Consultant Respiratory Physician had significant co-morbidities at initial interview, but subsequently were followed up by the pharmacist. Of the 51 patients, 50 started therapy and 1 patient did not attend the appointment. 9 (18%) patients reported adverse drug reaction. 46 (92%) patients successfully completed treatment, 3 (6%) patients did not complete therapy due to side effects and 1 (2%) patient was lost to follow up. The patient who did not attend subsequently developed active TB during the study period. Of the 9 adverse drug reactions reported, only 3 required treatment to be discontinued. No adverse drug reaction occurred due to drug interaction. Conclusion: A pharmacy-led clinic for LTBI is feasible and safe. Patients were happy to be seen by the pharmacist. Patients with poly-pharmacy benefited as they had a medication review to maximise therapy and reduce adverse drug reactions.